REFLEXÕES SOBRE A VIOLÊNCIA: poder e dominação nas relações sociais de sexo - Virginia Paes Coelho (Universidade Federal do Maranhão, 2014)
This article analyzes the institutionalization of violence in the context of gender relations. It is centered on the socio-cultural structure and how values, behaviors and attitudes arise that conform bodies according to each sex, leading to consequences such as inequality and intolerance, influencing the multiplicity of violent actions against the other. Masculine domination and the various expressions of gender violence that are perpetuated in society are the main results of the patriarchal ideology with serious inferences in the construction of gender identities. The deconstruction of all forms of violence is proposed, with respect for the other’s right to be a free subject in their sexual orientations and as a forming principle of human action.